Robotic-assisted versus standard laparoscopic radical cystectomy in bladder cancer: A systematic review and meta-analysis - Long, Junhao; Wang, Li; Dong, Ni; Bai, Xiaoli; Chen, Siyu; Sun, Shujun; Liang, Huageng; Lin, Yun (Frontiers in Oncology, 2022)
Background: This study aimed to evaluate the efficacy and safety of robotic-assisted radical cystectomy (RARC) versus laparoscopic radical cystectomy (LRC) in the treatment of bladder cancer. Methods: Two researchers independently searched PubMed, Embase, Cochrane, and CBM using the index words to identify the qualified studies which included randomized controlled trials (RCTs) and non-randomized controlled trials (prospective and retrospective studies), and the investigators scanned references of these articles to prevent missing articles. Differences in clinical outcomes between the two procedures were analyzed by calculating odds risk (OR) and mean difference (MD) with an associated 95% confidence interval (CI). Results: Sixteen comparative studies were included in the meta-analysis with 1467 patients in the RARC group and 897 patients in the LRC group. The results indicated that RARC could significantly decrease blood loss (P = 0.01; MD: -82.56, 95% CI: -145.04 to -20.08), and complications 90 days or more after surgery, regardless of whether patients were Grade ≤ II (P = 0.0008; OR: 0.63, 95% CI: 0.48 to 0.82) or Grade ≥ III (P = 0.006; OR: 0.59, 95% CI: 0.40 to 0.86), as well as overall complications (P: 0.01; OR = 0.52; 95% CI: 0.32 to 0.85). However, there was no statistical difference between the two groups at total operative time, intraoperative complications, transfusion rate, short-term recovery, hospital stay, complications within 30 days of surgery, and bladder cancer-related mortality. Conclusions: The meta-analysis demonstrates that RARC is a safe and effective treatment for bladder cancer, like LRC, and patients with RARC benefit from less blood loss and fewer long-term complications related to surgery, and should be considered a viable alternative to LRC. There still need high-quality, larger sample, multi-centric, long-term follow-up RCTs to confirm our conclusion.